2018
DOI: 10.1177/2164956118784902
|View full text |Cite
|
Sign up to set email alerts
|

Total Lifestyle Coaching: A Pilot Study Evaluating the Effectiveness of a Mind–Body and Nutrition Telephone Coaching Program for Obese Adults at a Community Health Center

Abstract: BackgroundStress and obesity are interrelated and common among low-income adults. Mind–body interventions have been shown to reduce psychological distress and have been incorporated into many weight loss interventions. However, few of these programs have incorporated a telephone coaching component.ObjectiveWe designed and piloted a novel weight loss telephone coaching intervention for this population and examined its effectiveness on weight loss and improvements in health behaviors in obese community health ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
14

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 40 publications
0
8
0
14
Order By: Relevance
“…Historically, integrative medicine services have been delivered in-person with telehealth-delivery playing only a small role, typically limited to intervention trials. 1 4 Barriers to telehealth-delivery of services exist across patient and provider levels, including lack of payment models, delivery platforms, health and technological literacy, and provider buy-in. 5 , 6 Integrative medicine prioritizes an authentic, healing relationship between patient and provider, one barrier frequently cited is the concern that virtual modalities may harm rapport.…”
mentioning
confidence: 99%
“…Historically, integrative medicine services have been delivered in-person with telehealth-delivery playing only a small role, typically limited to intervention trials. 1 4 Barriers to telehealth-delivery of services exist across patient and provider levels, including lack of payment models, delivery platforms, health and technological literacy, and provider buy-in. 5 , 6 Integrative medicine prioritizes an authentic, healing relationship between patient and provider, one barrier frequently cited is the concern that virtual modalities may harm rapport.…”
mentioning
confidence: 99%
“…Our search strategy identified 16,701 potentially relevant articles, of which 70 (45 RCTs 24–68 and 25 UBAs 69–93 ) met the inclusion criteria for this SLR with MA (Figure S1). Seventy‐six percent of the studies were published in the last 10 years, and most of them were conducted in Europe ( n = 26) and North America ( n = 24) compared to Oceania, Asia and South America.…”
Section: Resultsmentioning
confidence: 99%
“…In the current analyses, prescriptive dietary approaches were more effective than behavioural approaches in decreasing anthropometric measures among subjects with overweight and obesity when UBAs were considered. Prescriptive dietary interventions of the studies were based on individualized dietary plans mostly delivered by dietitians, nutritionists and/or experienced nurses 69,70,77,80,81,86,90 ; whereas in several studies based on behavioural approach, an individualized dietary plan was not delivered 71,72,76,78,79,82,83,85,88,89,93 . In this sense, a systematic review by Wadden et al 16 demonstrated that behavioural counselling is efficient for patients with overweight/obesity recruited from PHC.…”
Section: Discussionmentioning
confidence: 99%
“…As early as 2008, Eakin and coworkers (15) published one of many studies that demonstrate adults patients, even from disadvantaged communities, can achieve modest improvements in diet and physical activity though a telephone delivered intervention-as good and sometimes even better than face-toface counseling (16)(17)(18)(19)(20)(21)(22)(23). Nutrition care delivered via telephone for other conditions, too, have been found to be effective (24)(25).…”
Section: Telephone and Telehealth Cases 1-4 Revisitedmentioning
confidence: 99%